Surface Modification of Heterojunction with Intrinsic Thin Layer Solar Cell Electrode with Organosilane - Bing-Mau Chen; Chih-Hung Chen; Shang-Ping Ying (Micromachines)
Solar cell (SC) technologies, which are essential in the transition toward sustainable energy, utilize photovoltaic cells to convert solar energy into electricity. Of the available technologies, heterojunction with intrinsic thin-layer (HIT) solar cells offers high efficiency and reliability. The current study explored the enhancement of HIT solar cell performance through the use of 3-aminopropyltrimethoxysilane (APTMS) self-assembled monolayers (SAMs) on the surface of the cells’ indium tin oxide (ITO) layer. Photoluminescence mapping revealed greater brightness and photocurrent in the HIT sample treated with APTMS SAMs, with the results indicating more favorable optical and electrical properties. The application of APTMS SAMs led to higher open-circuit voltage, fill factor, maximum power output, and efficiency by passivating the ITO surface and achieving energy level alignment, thereby enhancing the charge carrier dynamics. These findings demonstrate the potential of APTMS SAMs to improve HIT solar cell efficiency and reliability.